2017
DOI: 10.1007/s00415-017-8593-x
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte and Alzheimer’s disease

Abstract: The past several decades have given rise to more insights into the role of astrocytes in normal brain function and diseases. Astrocytes elicit an effect which may be neuroprotective or deleterious in the process of Alzheimer's disease (AD). Impairments in astrocytes and their other functions, as well as physiological reactions of astrocytes to external injury, can trigger or exacerbate hyperphosphorylated tau and amyloid-beta (Aβ) pathologies, leading to the formation of both amyloid plaques and neurofibrillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 77 publications
1
46
0
Order By: Relevance
“…Also, astrocyte neuroprotective functions may have major therapeutic relevance for AD. In fact, glial cell dysregulation has been suggested as a possible cause of AD [11,24]. In the present study, we demonstrated that sAPPα produced by astrocytes in response to mGlu3R activation could act in a paracrine or autocrine fashion to stimulate Aβ uptake by astrocytes.…”
Section: Discussionsupporting
confidence: 57%
“…Also, astrocyte neuroprotective functions may have major therapeutic relevance for AD. In fact, glial cell dysregulation has been suggested as a possible cause of AD [11,24]. In the present study, we demonstrated that sAPPα produced by astrocytes in response to mGlu3R activation could act in a paracrine or autocrine fashion to stimulate Aβ uptake by astrocytes.…”
Section: Discussionsupporting
confidence: 57%
“…The exercise-induced cognitive improvements in AD mice is often associated with modulation of neuroinflammation [ 7 ]. Glial activation is a well-described feature of the AD brain [ 8 ], manifested as altered cell morphology [ 9 , 10 ] and function [ 11 ]. Both astrocytes and microglia are implicated in AD progression [ 1 ] and recent cell type-specific gene expression data have undoubtedly provided evidence for the strong involvement of astrocytes in human AD [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence demonstrates that impairment in astrocyte reaction to external injury can trigger or exacerbate hyperphosphorylation of tau as well as Aβ pathologies, leading to neuronal dysfunction. 88 Despite independent roles in neuroinflammation, there is growing evidence for intense interactions between microglia and astrocytes in AD. 89 First, microglia-secreted cytokines can activate astrocytes, which leads to loss of physiological functions and become neuronal toxicity.…”
Section: Neuroinflammationmentioning
confidence: 99%